2012
DOI: 10.1136/bmjspcare-2012-000196.61
|View full text |Cite
|
Sign up to set email alerts
|

Living and dying with cancer in Thailand

Abstract: Background Cancer is a leading cause of death in Thailand. Thai cancer patients often seek medical treatment while in advanced stages of the disease. Despite a recent increase in this attention given to improve end of life care in Thailand, little research has been undertaken to describe the experiences of those who live at the end of life. Aims The aim of this longitudinal ethnographic case study was to explore the experiences of living toward end of life in patients with advanced cancer. Methods Series i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In 2006, palliative care was implemented into the hospital accreditation standard by the Healthcare Accreditation institutes. [910] Meanwhile, the Ministerial Notification of Ministry of Public Health No. 197 B.E.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, palliative care was implemented into the hospital accreditation standard by the Healthcare Accreditation institutes. [910] Meanwhile, the Ministerial Notification of Ministry of Public Health No. 197 B.E.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, the leading cause of death is cancer. As a result of the number of cancer-related deaths in Thailand, palliative care has become an important aspect of health care and is now recognized as a quality indicator by the Thailand National Hospital Accreditation Authority (Nilmanat et al, 2010; Nilmanat & Phungrassami, 2006). Since cancer patients have been the recipients of the majority of palliative care in Thailand, it would be important to explore if there are differences in the palliative care interventions rated as important by nurses in cancer center versus noncancer center settings.…”
Section: Introductionmentioning
confidence: 99%
“…While studies have shown the effectiveness of home-based palliative care in countries where it is integrated into mainstream medicine, Thailand’s palliative care services primarily focus on hospital settings, with limited integration into community care [ 7 , 8 ]. To expand palliative care coverage, there is a need to enhance community and home-based palliative care programs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%